MENCIPTAKAN BRAND AWARENESS IKLAN MEDIA MASSA CETAK - D. Hagijanto, Andrian (Nirmana, 2001)
Although printed media has been sharply segmented, even sharper than television, the design elements are still need to be organized. The considered elements are the size, type, and the illustration of the ad. Since printed media characteristically used as supporting media in advertising campaign, it must have consistency in creative approach with the main media in order to maintain the continuity to gain brand awareness. Abstract in Bahasa Indonesia : Walaupun media cetak sudah tersegmentasi lebih tajam dibanding media televisi, tetap diperlukan suatu pengorganisasian elemen-elemen desain iklannya. Aspek-aspek yang perlu diperhatikan menyangkut perihal format, teks, dan ilustrasi iklan. Karakter media cetak yang seringkali dipakai sebagai media pendukung dalam kampanye periklanan, menjadikannya iklan media massa cetak harus mempunyai konsistensi konsep pendekatan kreatif yang konsisten dengan media utamanya agar tujuan pencapaian brand aware senantiasa terjaga. Printed media advertisement, brand awareness, printed ad it characteristic.